The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5152/akd.2014.4686
|View full text |Cite
|
Sign up to set email alerts
|

Relation of presence and severity of metabolic syndrome with left atrial mechanics in patients without overt diabetes: a deformation imaging study

Abstract: Objective: We aimed to investigate left atrium (LA) function by speckle tracking echocardiography in patients with metabolic syndrome (MetSyn) and to show a possible relationship between the severity of MetSyn and LA function and to determine the predictors of low strain in MetSyn patients. Methods: Our study design was observational and cross-sectional design consisted of 80 MetSyn patients without overt diabetes and 50 controls. The patients were classified into three groups based on the number of MetSyn cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Interestingly, Kurt et al showed that metabolic syndrome was independently associated with decreased LA strain, whereas individual criteria were not proven to be the independent predictors of reduced LA strain. 32 In the whole study population, we did not find any relation between atrial phasic function and 24-hour heart rate, which is line with findings from the literature, 30 and in our case could be explained by a relatively small-normal range of 24-hour heart rate values that is perhaps responsible for the lack of statistically significant results. Decreased LA strain in our investigation is clinically very important because recent studies demonstrated that LA strain and strain rates represent independent predictors of stroke, transitory ischemic attack, and heart failure in patients with atrial fibrillation that is usually associated with hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, Kurt et al showed that metabolic syndrome was independently associated with decreased LA strain, whereas individual criteria were not proven to be the independent predictors of reduced LA strain. 32 In the whole study population, we did not find any relation between atrial phasic function and 24-hour heart rate, which is line with findings from the literature, 30 and in our case could be explained by a relatively small-normal range of 24-hour heart rate values that is perhaps responsible for the lack of statistically significant results. Decreased LA strain in our investigation is clinically very important because recent studies demonstrated that LA strain and strain rates represent independent predictors of stroke, transitory ischemic attack, and heart failure in patients with atrial fibrillation that is usually associated with hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Speckle-tracking echocardiography (STE) is a non-Doppler, angle-independent technique allowing the measurement of global and regional atrial strain (6, 17). Several studies have already proved the usefulness of LA STE in sinus rhythm (12, 18) and in AF (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…15 The evaluation of LA function with two-dimensional strain imaging has only recently been proposed. 1,3,[16][17][18] There are two different strain values used in the evaluation of LA functions by strain imaging: the peak strain at LA reservoir phase and the strain value measured just before the P-wave at LA pump function phase. 19 LA reservoir functions are mainly determined by LV-systolic functions and LA stiffness.…”
Section: Discussionmentioning
confidence: 99%